Culture and “Francophonie Games - Gloria Mayen Umukoro; Dorathy Effiom Okon; Mamina Mba Diffon; Grace John Ibat (Fakultas Ilmu Sosial dan Ilmu Pendidikan Universitas Tadulako, 2021)
This study exploits the idea of rethinking culture in Francophonie games using the survey research design. Francophonie games is conceptualized into sports and cultural competitions and rethinking culture into physical and non-physical aspects of cultural modifications. Three specific objectives are developed on the basis of the research problem as follows (1) Identify the relationship between the ‘Francophonie games’ and the dissemination of the French language (2) identify the various rethinking culture modifications borne out of the Francophonie games, (3) determine the moderating influence of race on rethinking culture and “Jeux de la Francophonie”. Participating athletes in the last concluded “Jeux de la Francophonie” held in Abidjan were interviewed. Secondary sources of data also considered. Findings reveal that the Francophonie games is not a driving factor for the dissemination of the French language among non-French speakers. In addition, sports competition with physical rethinking culture, culture completion has no significant relationship with non-physical rethinking culture in “Jeux de la Francophonie”, and that race does not play a moderating influence in rethinking culture and Francophonie games. The study recommends among other things the introduction of variety of cultural games like voodoo, traditional cooking competition, traditional fashion parade etc. in order to boost culture rethinking via sports.